Viability of the head louse eggs in pediculosis capitis. A dermoscopy study. - Scanni, G.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
The dermoscope without fluid may be useful to establish the viability of a head louse colony by differentiating viable head louse eggs from aborted eggs and from hatched empty nits, irrespective of their distance from the scalp. A nit, the metabolism of which stopped spontaneously or as a consequence of treatment, is characterized by a longitudinal or roundish depression of its wall -abortive dimple-.